A detailed analysis on the use of gamification in cloud based learning management systems - Wan Ab.Rahman, Wan Nurhayati; Rana, Muhammad Ehsan; Rahman, Muhammad Ahsan (Little Lion Scientific, 2019)
The concept of infusing game elements into non-game applications has been gaining momentum as of lately.In this paper we explore and identify the variables which affect learning experience and how knowing those can help in implementing game mechanics on a Learning Management System (LMS) which is flexible in nature in its operations so that it can be scaled as required using cloud infrastructure. This research tries to assess how, why and where gamification and cloud computing should be best utilized in the context of learning management systems by exploring both existing learning management systems using game mechanics and outlook of how gamification can be used to propel students’ overall learning experience